Pengembangan Roller Math untuk Pesenam Artistik Pemula di Jawa Tengah - Putri, Dwi Tiga; Soenyoto, Tommy; Raharjo, Agus; Adi , Adi; Darmawan, Agus; Billiandri, Bhayu (Universitas Hamzanwadi, 2025)
The background of this research is the lack of supporting facilities for artistic gymnastics achievements owned by clubs in Central Java. The purpose of this research is to develop roller math that can be used for basic gymnastics technique training, especially for beginner athletes in Central Java. The research method uses R&D using 10 steps of research and development. The small-scale test used a sample of 10 athletes, while the broad-scale test used 30 athletes. The expert validation sheet instrument was used to validate the initial product and the questionnaire was used to collect small-scale test data and broad-scale tests. Data analysis using percentage description. The results of the initial product validation of the roller math tool from 2 artistic gymnastics experts and 2 equipment experts. The results of the average score of gymnastics expert 1 score 93, gymnastics expert 2 score 92, equipment expert 1 score 92 and equipment expert 2 score 93. The development of roller math tools can be used for front roll, flic flac, hand spring exercises. Expert validation shows a score of 92% which means the tool can be continued for the field trial process. The results of the field trial showed a tool acceptance rate of 87.25%. It is concluded that the roller math tool can be used for training beginner athletes in Central Java.